Immunopathogenesis of infectious-inflammatory diseases of central nervous system - G. F. Zheleznikova; N. V. Skripchenko (Журнал инфектологии)
The revue includes the contemporary information about the role of resident cells of the CNS (astrocytes, microglia) in development of innate immune response against pathogen (or its products) invasion in the brain. The detection of invading pathogens by pattern-recognition (Toll-like) receptors of neuroglia is described. Also is described the production by these cells of inflammatory mediators, including proinflammatory cytokines, as well as inflammation downregulating factors that protect the CNS from alteration and degeneration.